Pharmaceutical care in community pharmacies in Jordan: a public survey - Mukattash TL; Bazzi NH; Nuseir KQ; Jarab AS; Abu-Farha RK; Khdour MR. (Centro de Investigaciones y Publicaciones Farmaceuticas, 2018)
Objective: This study aims to assess the views and attitudes of the general public towards the current role of pharmacists in Jordan. Methods: This study is a cross-sectional quantitative questionnaire-based study. After a thorough literature review on public perspectives of pharmaceutical care services, a draft questionnaire was designed. This questionnaire was examined and discussed in a focus group of invited public members and was amended accordingly to reach the final draft. The questionnaire was administered using a structured interview technique in which members of the public were asked a series of questions by a trained pharmacist. The study took a place over a period of six months, from January to June 2013. Individuals were recruited from urban and rural areas of Jordan. Results: A total of 1214 respondents were interviewed during the study. Of the respondents, 67.8% were female. Most of the respondent were married (64%) and had a university degree (88.5%). Approximately half of the respondents (55.1%) had no previous knowledge of pharmaceutical care. A relative majority of respondents considered the most important activity performed by pharmacists to be dispensing medications (46.2%), followed by patient counseling (34.6%). The majority of respondents (86.4%) believed that pharmacists have a role in providing healthcare services, and 68% of respondents reported that in order to serve their needs, a pharmacist must consider the patient's needs and engage patients in determining medication timing and options. Conclusions: The plurality of respondents believed in the importance of pharmacists in providing pharmaceutical care services. However, respondents expected much from pharmacists and felt that their current role was unsatisfying.